Nilai Tawakkal dalam Al-Qur'an - Nurmiati Nurmiati; Achmad Abubakar; Aan Parhani (Palita: Journal of Social Religion Research, 2021)
Abstract[English]:This article discusses the value of Tawakkal in the Qur'an and is written using the thematic interpretation method. In his analysis, the author first determines the topic, then looks for verses related to the topic and continues by reviewing the collected verses. The Qur'an mentions many verses related to the commandment to believe in Allah and surrender all results after earnest effort. The term tawakkal is mentioned 68 times in the Qur'an in 60 verses and in 20 different suras. From the whole verse, it is revealed that the word tawakkal contains five values, namely the first is piety to Allah after an important decision, the second is steadfastness towards the enemy, the third is tawakkal supports peace, the fourth is trustworthiness, and the fifth is the promise of goodness. God to those who believe in Him.Abstrak[Indonesia]:Artikel ini membahas tentang nilai Tawakkal dalam Al-Qur'an dan ditulis dengan menggunakan metode tafsir tematik. Dalam analisisnya, penulis terlebih dahulu menentukan topik, setelah itu mencari ayat-ayat yang berkaitan dengan topik dan dilanjutkan dengan mengulas ayat-ayat yang terkumpul. Al-Qur'an menyebutkan banyak ayat yang berkaitan dengan perintah untuk percaya kepada Allah dan menyerahkan semua hasil setelah usaha yang sungguh-sungguh. Istilah tawakal disebutkan 68 kali dalam Alquran dalam 60 ayat dan dalam 20 surah yang berbeda. Dari keseluruhan ayat tersebut terungkap bahwa kata tawakal mengandung lima nilai, yaitu pertama ketakwaan kepada Allah setelah keputusan penting, kedua tawakkal adalah ketabahan terhadap musuh, ketiga tawakkal mendukung perdamaian, keempat amanah, kelima ada janji kebaikan. Allah kepada orang-orang yang percaya kepada-Nya.